A Study on the Various Programs Initiated By Indian Government to Promote Girl’s Education: Exploring Initiatives by the Indian Government to Promote Girl's Education (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The significant social changes that India has seen over the most recent couple of decades or so have influenced its whole populace, yet in some underestimated segments of its general public their effect has not been much amazing. The changed financial conditions, especially after freedom, have seen open doors for girls to got training and work, and have furnished them with new roads to express and attest their correspondence.The explanation behind this can be sorted as outside, inside and financial and mental. The outside limitations ate identified with the issues and troubles at the approach level, arranging, and execution and at organization level. The current paper highlights the programs initiated by Indian government to promote the education of the girls.